Mastocytosis. - Dirk Van, Gysel; Arnold P., Oranje (European Journal of Pediatric Dermatology, 2008)
The Authors review the classification, diagnostic and therapeutical criteria of mastocytosis in children and adults, according to the recent international guidelines.